2012
DOI: 10.1016/j.aat.2012.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic efficacy of tramadol/acetaminophen and propoxyphene/acetaminophen for relief of postoperative wound pain

Abstract: Among patients with mild to moderate postoperative wound pain, single-dose Ultracet can provide slightly better analgesic efficacy than Depain-X in terms of onset and duration. Depain-X is no longer marketed in Europe, America, Taiwan and other countries, therefore, Ultracet can serve as a good substitute for treating postoperative pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In postoperative pain treatment, the administration of drugs with side effects that require interventions and disrupt the patient's vital functions increase costs and require additional staff, all of which limit their use. Recent studies showed that paracetamol is an analgesic with few side effects, a wide dosage range, and easy use (16,23). Tramadol is an opioid with few side effects also and it is thought to have good analgesic activity (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In postoperative pain treatment, the administration of drugs with side effects that require interventions and disrupt the patient's vital functions increase costs and require additional staff, all of which limit their use. Recent studies showed that paracetamol is an analgesic with few side effects, a wide dosage range, and easy use (16,23). Tramadol is an opioid with few side effects also and it is thought to have good analgesic activity (24).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that paracetamol is an analgesic with few side effects, a wide dosage range, and easy use (16,23). Tramadol is an opioid with few side effects also and it is thought to have good analgesic activity (24).…”
Section: Discussionmentioning
confidence: 99%
“…Another opioid, tramadol (TRAM), has been a suitable alternative for many patients. This has been reviewed thoroughly elsewhere …”
Section: Introductionmentioning
confidence: 99%
“…Studies by Grundmann et al and Lin et al showed paracetamol to be an analgesic with few side eff ects, wide dosage range and easy use 41,42 . Cakan et al studied the effi cacy of paracetamol following lumbar disc surgery and concluded that paracetamol decreased visual analog scale (VAS) scores but did not decrease morphine consumption 29 .…”
Section: Fig 1 Diff Erences In Pain Perception Between Study Groupsmentioning
confidence: 99%